2022
DOI: 10.1155/2022/9986587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Benson Relaxation Technique and Music Therapy on the Anxiety of Primiparous Women Prior to Cesarean Section: A Randomized Controlled Trial

Abstract: Background and Aims. Primiparous women experience high levels of anxiety before cesarean section. Therefore, this research aimed to investigate the effects of the Benson Relaxation Technique (BRT) and Music Therapy (MT) on the anxiety of primiparous women prior to cesarean section. Methods. A randomized controlled trial was carried out on 105 women scheduled for cesarean section. They were randomly assigned into three groups: BRT, MT, and control (n = 35 per group). The women in the BRT and MT groups performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In summary, this review showed that most but not all the included studies found that music was beneficial in reducing pain and anxiety during vaginal labour [3,27,[38][39][40][41][42][43][44][45][46][48][49][50][51][52][53] and C-section [13,14,56,57,[59][60][61], particularly in primiparous women. However, other studies did not find a significant advantage of music over a control condition or a different therapy [47,58,60].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In summary, this review showed that most but not all the included studies found that music was beneficial in reducing pain and anxiety during vaginal labour [3,27,[38][39][40][41][42][43][44][45][46][48][49][50][51][52][53] and C-section [13,14,56,57,[59][60][61], particularly in primiparous women. However, other studies did not find a significant advantage of music over a control condition or a different therapy [47,58,60].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The application of music as one element of a larger treatment during vaginal labour [27,53], as individually selected music [41,52,54,55], as music combined with another therapy [27,[51][52][53], as instrumental [3,14,40,43,46,48], classical [13,42,53] and relaxing [27,42,45,50,51,57,59,60] styles of music, and as music played via headphones during the caesarean procedure [14,54,57,[59][60][61] all seemed particularly helpful in reducing pain and anxiety in mothers.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations